2014
DOI: 10.1002/pri.1590
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Practice Exposure and Physiotherapy Students' Behaviour during Clinical Placements: A Survey

Abstract: Background and purpose. Physiotherapists are expected to practice in an evidence-based way. Evidence-based practice (EBP) should be an integral part of the curriculum to ensure use of the five EBP steps: asking clinical questions, searching for and appraising research evidence, integrating the evidence into clinical practice and evaluating this process. The aim of this study was to compare self-reported EBP behaviour, abilities and barriers during clinical placements reported by five cohorts of final year phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 38 publications
(67 reference statements)
2
48
0
1
Order By: Relevance
“…They found that students who were exposed to more teaching in evidence-based practice more often conducted a critical review of research than those who were exposed to less teaching in evidence-based practice. However, in clinical situations involving patients, there was no difference in terms of how the students utilised research-based knowledge (Olsen et al, 2014). Although students tried to use an evidence-based approach, they felt uncertain, as novices in clinical practice, about how to actually go about doing it.…”
Section: Conflicting Logics Behind the Evidencebased Practice Modelmentioning
confidence: 99%
“…They found that students who were exposed to more teaching in evidence-based practice more often conducted a critical review of research than those who were exposed to less teaching in evidence-based practice. However, in clinical situations involving patients, there was no difference in terms of how the students utilised research-based knowledge (Olsen et al, 2014). Although students tried to use an evidence-based approach, they felt uncertain, as novices in clinical practice, about how to actually go about doing it.…”
Section: Conflicting Logics Behind the Evidencebased Practice Modelmentioning
confidence: 99%
“…This implies that EBP is asked for in student's work, including in the exams throughout the three years of education. The students attended approximately 10 hours of EBP teaching before their second-year clinical placement, which can be defined as low level exposure of EBP teaching according to Olsen et al (5). The students were not, before this study, required to apply EBP work to the clinical placement period.…”
Section: Description Of Ebp Teaching On the Bachelor Programmesmentioning
confidence: 99%
“…Healthcare students report various barriers to EBP during clinical placements, which include lack of time, high workload, lack of support during clinical placements, students and clinical instructors prioritizing hands-on experience during clinical placements, lack of role models in clinical placements and insufficient autonomy to change practice (1,(4)(5)(6)(7). Stronge and Cahill (1) examined the knowledge, attitudes and behaviours of occupational therapy bachelor's students towards EBP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations